FEATURES OF REALIZATION of the process approach in quality management systems of EDUCATIONAL INSTITUTIONS - Vladimir A. Ivanov; Alevtina V. Selezneva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The features of the realization of the process approach in quality management systems of educational institutions are presented at the article. The problems of the creating effective quality management system based on higher education institutions are considered. The different approaches to management are analyzed and the benefits of quality management systems based on the process approach and brought to the requirements of ISO 9001 (International standardization organization) are identified. The definitions of the terms "service" and "products" in relation to higher education institutions are given. The unique to the quality management system of the university processes are indentified and the possible indicators of its effectiveness and efficiency as an example of the Perm National Research Polytechnic University (PNRPU) are developed.